(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Schiff bases are considered as privileged ligand in coordination chemistry as they easily form stable complexes with most transition metal complexes. In this paper, a novel Schiff base ligand derived from Thiophene-2-carboxaldehyde (TPC) and 4,4’ diamino diphenyl methane (DDM) and its transition metal complexes Cu(II), Zn(II), Co(II) and Ni(II). Antimicrobial, antioxidant, anti-inflammatory, larvicidal, DNA cleavage activity against standard at variable concentrations revealed that the Cu(II), Zn(II), Co(II) and Ni(II) complexes show enhanced antimicrobial, free radical scavenging and anti-inflammatory activities as compared to TPC and DDM.